Evaluation of Two Decades of Fiscal Decentralization on Economic Capacity and Community Welfare: A Case Study of Bengkulu Province - Dheanggi Wulan Pratama Wanty; Septriani Septriani (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study examines the impact of fiscal decentralization on local economic capacity and the welfare of the people of Bengkulu over the past two decades. Bengkulu was chosen as a case study because it has the second highest poverty rate in Sumatra Island. The study uses time series data obtained from various secondary sources, such as the human development index, poverty reports, DAU, and provincial economic development reports. This study uses a partial least squares structural equation model (PLS-SEM) using SmartPLS 3 software to analyze the data. This study has three main variables: community welfare (Y), economic capacity (M), and fiscal decentralization (X). The results of this study show that fiscal decentralization has an indirect effect on community welfare but a direct effect through economic capacity.